2019
DOI: 10.1136/archdischild-2019-317635
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of pulmonary tuberculosis in children in Mainland China, 2009–2015

Abstract: ObjectiveTo describe the incidence and epidemiological characteristics of child pulmonary tuberculosis (PTB) notified to the Chinese Center for Disease Control and Prevention (CDC) Tuberculosis Information Management System (TBIMS) from 2009 to 2015.Study designA database of child PTB for 31 provinces in mainland China over 7 years was retrospectively analysed. The spatiotemporal distribution of child PTB was described.ResultsIn total, 35,710 child PTB cases were notified to the TBIMS, representing only 0.60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…However, the actual TB burden in children remains uncertain [7,8]. According to the Chinese CDC report, the average annual incidence of PTB in children was reported at 2.44/10 5 [2]. Compared with other countries, the incidence was lower than that of some countries, such as Cambodia and India [1], but still higher than the average global level [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the actual TB burden in children remains uncertain [7,8]. According to the Chinese CDC report, the average annual incidence of PTB in children was reported at 2.44/10 5 [2]. Compared with other countries, the incidence was lower than that of some countries, such as Cambodia and India [1], but still higher than the average global level [9].…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO global TB report 2019, an estimated 10.0 million (range: 9.0–11.1 million) people fell ill with TB in 2018 globally, and children accounted for 11% [ 1 ]. Fortunately, a recent study employing data from the Centers for Disease Control (CDC) found that, in China, from 2009 to 2015, the incidence of pulmonary TB (PTB) in children decreased by over 50% [ 2 ]. Similarly, the data extracted from the Global Health Data Exchange showed that from 1990 to 2017, decreasing trends in prevalence (average annual percent change: −0.5%), incidence (−3.2%) of all tuberculosis cases were observed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterial cultures are the gold standard for diagnosing TB but are imperfect in children. Data from 35,710 children of pulmonary TB reported to the Chinese Center for Disease Control and Prevention [17] and 1212 hospitalized children with active TB [14] showed only 21.7% and 14.4% positivity rates, respectively, on bacteriological tests. Previous studies reported various culture yields in childhood tuberculosis cases; these yields depended on several factors, including age, disease severity, specimen type and quality, and culture method used [18].…”
Section: Discussionmentioning
confidence: 95%
“…In China, the incidence of pulmonary TB in children less than 15 years of age was 0.00244% between 2004 to 2015. 15 Extrapulmonary TB was not included in this survey, and the incidence of TB may be much higher in pediatric HSCT recipients than that in the general pediatric population. Therefore, our patients were carefully screened for TB before HSCT and high-risk patients received prophylactic TB treatment.…”
Section: Discussionmentioning
confidence: 99%